Characteristics of the stalking campaign: Consequences and coping strategies for men and women that report their victimization to police - Acquadro Maran, Daniela (PLoS One, 2020)
The study analysed cases reported to police by men and women who were victims of stalking. The objective was to describe the characteristics of the stalking campaigns experienced by men and women, their consequences, and the coping strategies adopted by the victims, as they are recorded in police case files. All the information was collected in three cities in the Northwest of Italy. Analyses were performed on 271 files classified by police officers as cases of stalking, reported by men (87, 32.1%) and women (184, 67.9%). The study revealed that men tended to let the stalking campaign last for a longer time than women before turning to the police. Procrastination had some consequences, especially in the emotional sphere, that affected the victim’s wellbeing. Moreover, the coping strategies used by men victims were not effective and even risked to hamper the work of the police officers intervening and investigating on the case.